Development and validation of an economic, environmental friendly and stability-indicating analytical method for determination of ampicillin sodium for injection by RP-HPLC - Tótoli, Eliane Gandolpho [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2014)
Ampicillin is an antimicrobial agent widely used in many parts of the world and recommended by the World Health Organization. Considering its importance on the global scene, the development of optimized analytical methods for the quality control of ampicillin is essential, seeking the therapeutic efficacy, patientÂ´s safety and also benefits for the pharmaceutical industry. In this context, it was developed a new analytical method by RP-HPLC for the analysis of ampicillin sodium in powder for solution for injection. It was used a very simple mobile phase, comprised by a mixture of ethanol and water, pumped at a flow rate of 0.5 mL min-1. The method was validated according to ICH guidelines, showing it to be linear, precise, robust, accurate and specific, over a concentration range of 70-120 Î¼g mL-1. It also showed to be stability indicative. Therefore, the validated method is suitable for quantifying ampicillin sodium in powder injectable solution and to determine its stability. Furthermore, the analysis is fast, which contributes to an economy of solvents and a less generation of organic waste and ethanol is an organic solvent easier to dispose and less toxic than those most commonly used for chromatographic analysis. For these reasons, the developed method can be a more economical, safer and environmentally friendly alternative for the analysis of ampicillin sodium.
Keywords: Ampicillin sodium; Analytical method; Quality control; Reversed-phase chromatography; Ethanol